To what extent do the prevalence of sickness presence and reasons for sickness presence vary between school classes in upper secondary schools? A cross-sectional survey in Trøndelag county, Norway - Vegard Johansen (BMJ Open)
Objectives This paper investigated sickness presence (SP) among students in academic upper secondary schools (USS). The research question asked was: To what extent do the prevalence of SP and reasons for SP vary between school classes in USS in Norway?Design A cross-sectional survey was done in the final year of USS. Multilevel modelling was used to estimate school class-level effects.Setting 71 school classes from 13 Norwegian schools participated in the study in April 2018.Participants 1955 students in academic education programmes were invited to participate in the survey, and 1511 completed it. The response rate was 77%. 58% of the respondents were female students.Outcome measures The outcome measures were the number of SP incidents and reasons for practising SP in school. The analysis examined factors that influenced the prevalence of and reasons for SP.Results 54% of the students reported two or more incidents of SP. The primary reason for reporting SP was attendance pressure, including factors such as not wanting to exceed the absence limit (90%), concerns that high school absences could negatively affect grades (65%) or reduce chances of getting a job (61%). Some students reported positive reasons for SP, such as maintaining social connections (32%). Multilevel modelling indicated that the class-level effect on the prevalence of SP incidents and positive attendance reasons accounted for 5% of the variance. Some of the class-level effect was due to contextual factors (eg, student relations) and less was due to compositional factors (eg, gender distribution).Conclusions The study discovered significant variations in SP between school classes, suggesting that students’ attitudes and behaviours towards SP can influence their peers. Moreover, attendance pressure factors for SP were more frequently reported than positive attendance factors.